A Theory of Quantitative Easing Policy and Negative Interest Policy Based on the Japanese Experience - Otaki, Masayuki (Journal of Reviews on Global Economics, 2016)
Using a two-period overlapping-generations model, I elucidate how quantitative easing policy and negative interest policy affect an economy based on the Japanese experience under the Abe cabinet. Quantitative easing policy forces a huge amount of money hoarding. Accordingly, the rate of return for money is required to rise. This implies that disinflation and/or deflation are accelerated in Japan, which is in line with reality. On the other hand, quantitative easing policy stimulates the aggregate demand, which brings about a mild recovery in business. The business upturn tightens the foreign market because of an increase in imports and causes the home currency to depreciate. Negative interest policy implies there is a tax levied on money hoarding. Hence, as longas the government expenditure is kept constant, money circulating in an economy decreases, thereby discouraging business. Such a downturn reduces aggregate income and imports. This induces excess supply of foreign exchange. Consequently, the exchange rate appreciates to equilibrate the market. These characteristics of the business cycle in conjunction with changes in the attitude of the monetary authority are entirely consistent with the current Japanese experience under Abenomics.